The role of General Practitioner in the recognition of adrenal insufficiency - Marta Dudzińska; Agnieszka Zwolak; Joanna Malicka; Joanna Świrska; Ewa Kiszczak-Bochyńska; Robert Jan Łuczyk; Robert Zwolak; Jadwiga Daniluk; Jerzy Tarach (Kazimierz Wielki University, 2017)
Background. Addison's disease (AD), usually caused by an autoimmune process, has non-specific symptomatology. The deficiency of cortisol is manifested by weakness, anorexia, weight loss and orthostatic hypotension.  Early recognition is crucial as acute adrenal insufficiency is a life threatening state. Objectives. Analysis of the clinical picture, occurrence of symptoms before diagnosis, and the role of General Practitioner (GP) in the diagnosis of AD. Material and methods. 23 patients with primary adrenal insufficiency (18F, 5M, aged 24-80 years, with an average of 46,6 years). A method of proprietary questionnaire was used. Results. The symptoms present prior to diagnosis were as follows: weakness (100% of patients, approximately 9,2 months before the diagnosis), fatigue (100%; 8,8 months respectively), loss of appetite (95,6%; 9,1 months), skin darkening (95,6%; 10 months), orthostatic hypotension (91,3%; 10,7 months), weight loss (86,9%; 6,8 months), low blood pressure (73,9%; 11 months), stomachache (69,6%; 4,6 months), nausea (65,2%; 3,6 months), increased appetite for salt (56,5%; 6,2 months), muscle pain (52,2%; 15,5 months), hyperpigmentation of buccal mucosa and gums (47,8%; 2,7 months), vomiting (43,5%; 3,4 months). Because of these symptoms patients went to different specialists, including GPs in 78,3% of cases. Suspicion of the disease in 34.8% put GP. Conclusion. The symptoms of AD develop slowly and are present long time before the right diagnosis is established. Difficulties in early diagnosis may result from a low specificity of most of the symptoms. The role of GP in establishing the right and early diagnosis of Addison's disease is crucial.